Dampak Motivasi Kerja dan Kualitas Kehidupan Kerja (Quality of Work Life) terhadap Produktivitas Kerja Karyawan di PT. Mas Arya Indonesia - Sri Supriyati; Farikhatul Azizah; Eka Kurnia Patmasari (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
Employee productivity is a crucial factor in a company's success. This study aims to analyze the influence of work motivation and quality of work life on employee productivity at PT. Mas Arya Indonesia. A quantitative approach was employed, with a population consisting of all 4,000 employees. The sample was selected using the simple random sampling method, resulting in 98 respondents who met the criteria. Data collection was conducted through questionnaires and secondary data from the company, while data analysis utilized multiple linear regression with SPSS 22 software. The results indicate that work motivation has a positive impact on employee productivity, as evidenced by a t-count value of 3.698, which is greater than the t-table value of 1.6747 at a 0.05 significance level. Quality of work life also positively affects productivity, with a t-count value of 5.225 exceeding the t-table value. Simultaneously, work motivation and quality of work life significantly influence employee productivity, as shown by an F-count value of 65.710, higher than the F-table value of 2.79. The R-Square value of 0.572 suggests that 57.2% of productivity variations are influenced by these two variables. These findings emphasize the importance of enhancing motivation and creating a high-quality work environment to boost employee productivity.